Tenure Conflicts Resolution Of Colol Custom Community In Ruteng Recreation Park, Nusa Tenggara Timur - Rofii, Kriswoyo - (KOMUNITAS: International Journal of Indonesian Society and Culture, 2019)
AbstractDetermination of the Ruteng Recreation Nature Park had caused conflicts over tenure for Colol custom community have been in and around the area since before the establishment. Conflict was due forÃ‚Â  access to agricultural land use and timber had closed by the management. The conflict resolution involves three elements, namely the government, customs and religion which are called the three pillars. This study aims to understand the stages of the tenure conflict, relevant stakeholders and the conflict resolution. The study was conducted Colol village in April to May 2016. Acquisition of data using observation, in-depth interviews with a purposive and snowball and secondary data. Analysis of data using conflict tree analysis, stakeholders and mapping conflicts. The results showed that the cause of the conflict is the difference in value systems that implicates disagreement land status and boundaries as well as the uncertainty of access due to rights issues and access. Conflict resolution is required is to build trust between the parties, improve communication to reduce the differences in perception, increased involvement of indigenous peoples in the management of Ruteng Recreation Park, reconstruction of recreation park boundaries involving the parties, especially the major stakeholders and optimizing the coordination and communication between the parties.Colol Custom Community determine their traditional territory option to pull out of the Ruteng Recreation Park.Ã‚Â